Solução de conflitos: análise de dez casos - Dias, Murillo de Oliveira (2008)
The practice of the negotiation is old as well as the existence of the human being. According to Shell (1999) 'we negotiate many times in one day'. We negotiate every day on infinite subjects with people of the same culture or another total distinct one, in most diverse environments. The negotiation is so present in our lives that we negotiate at least something with someone every day, since wage increases until the construction of industrial plants overseas, in scenarios of political conflict. The general objective of this work is to understand why some of these negotiations are well-succeeded while others fail. In order to reach our goal, we need initially to describe what happens at the moment, or when the negotiation is occurring. However, just to describe the process in itself is not a great deal. It is important also to diagnosis what it is going on and to prescribe corrective or preventive solutions, as the case. The particular objective of this work is to provide answers to the following research questions: 1. Which is the profile of the Brazilian negotiator? 2. Do brazilians negotiate different subjects the same way? 3. How do the brazilians behave when facing other cultures?This work presents a survey, submitted successfully to the appreciation of hundreds of brazilians, with the objective to know how they behave in ten real situations with different scenarios, previously and carefully chosen and analyzed throughout the present work. Some results had been sufficiently curious. The reader is invited to explore such conclusions on the challenges faced by the Brazilians on ten scenarios mentioned.